The Effect of Leadership Style and Work Environment on Performance with Work Motivation and Job Satisfaction As Intervening Variables at the Mentawai Islands Regional Secretariat - Purba, Yan Richo Nielson; Heryanto (Archives of Business Research, 2019)
This study aims to examine the influence of leadership style and work environment on performance with work motivation and job satisfaction as an intervening variable at the Regional Secretariat of the Mentawai Islands Regency. The study population was 50 employees of the Regional Secretariat of Mentawai Regency. The sampling technique uses random sampling. The number of samples that can be used for analysis purposes are as many as 45 people. The hypothesis testing of the research is done by using path analysis statistical analysis techniques. The results of the study found that 1) The leadership style had a significant influence on employee job satisfaction. 2) The work environment has a significant influence on employee job. 3) The leadership style has a significant influence on employee motivation. 4) The work environment has a significant influence on employee motivation. 5) The leadership style has a significant influence on the performance of employees. 6) The work environment has a significant influence on the performance of employees. 7) Work motivation has a significant influence on the performance of employees. 8) Job satisfaction has a significant influence on employee performance. 9) Work motivation as an intervening variable gives a significant influence between leadership style and employee performance. 10) Work motivation as an intervening variable gives a significant influence between the work environment and employee performance. 11) Job satisfaction as an intervening variable gives a significant influence between leadership style and employee performance. 12) Job satisfaction as an intervening variable gives a significant influence between work environment and employee performance.